MỘT SỐ VẤN ĐỀ VỀ TÀI NGUYÊN VÀ MÔI TRƯỜNG TRONG PHÁT TRIỂN BỀN VỮNG Ở VIỆT NAM - Sơn, Nguyễn Danh (Nhà xuất bản Nông nghiệp, 2016)
Natural resources and the environment are one sustainable development pillar. From 2004 Vietnam has promulgated and implemented “The strategic orientation for sustainable development in Vietnam” (shortly Vietnam Agenda 21). In the last 6 years one has witnessed the country’s obvious and impressive achievements in the social and economic areas, but the environmental picture has not changed accordingly. It could not catch up with social and economic changes towards sustainable development. This is warned as an important reason for the country not being able to pursue sustainable development in the past and even for the years to come. This paper presents some issues on natural resources and the environment in sustainable development in Vietnam in relation to socio-economic development strategies for the last 10 years (2001-2010) and the 10 years to come (2011-2020) from 2 points of view: (i) natural resources and the environment as an essential resource of development; and (ii) natural resources and the environment as a sustainable development pillar. The paper is organized as follows: Part 1 begins with an overview of how natural resources and the environment were exploited, used and managed and how this has had impacts on the country’s development process towards sustainability. It then examines the connection between 3 sustainable development pillars. Part 2 provides some discussions on the connection between natural resources and the environment with economic growth and socio-economic development towards sustainability in the development strategy for the 10 coming years (2011-2020) of the country.